Technology as a factor in gender differentiation of work roles: a case study of Israel's smallholder co-operative villages - Nevo, Naomi (Journal of rural studies, 1991)
The paper deals with technology as a gender issue in Israel's moshavim. The subject is examined in the context of the household as well as the farm business managed and worked as a productive unit producing mainly for foreign markets. Data were collected by a combination of research methods including participant-observation techniques and classical anthropological open-ended interviews with informants in five moshavim. In times of rural economic prosperity, to which agricultural technological innovation is a contributing factor, women generally retreat into the home. The women's domestic world then becomes more sophisticated and demanding and technological innovations in the kitchen are commonplace. The branch of hothouse flower growing, however, characterized by technology, has to a great extent remained a woman's enterprise. Some women in these villages make careers of flower growing but there are intervening variables such as the husband's occupation and the family's economic circumstances. Despite the economic correlates, the field material points up the stereotypes. It is hypothesized that even flower growing may be part of the female stereotype which redresses the balance of the disinterest and incompetence attributed to women in technological matters. The main stereotype is one of aptitude and talent in technology which some men are ready to display in a sophisticated kitchen. This case study indicates that the crucial variable which influences gender differentiation in work roles is technology itself rather than the particular context of its application. At the same time it is clear that the man is able to transcend his stereotyped image more easily than the woman in the application of technology.